1993
DOI: 10.1093/jn/123.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Rat Adipose Tissue Cellularity Are Altered by Dietary Restriction and Exercise

Abstract: This study examined the effects of diet restriction and exercise training during aging on adipocyte size and number in male Wistar rats. An average of 30 weanling rats each were assigned to one of four experimental groups: ad libitum access to food, nonexercised; diet restricted, nonexercised; ad libitum access to food, exercised; diet restricted, exercised. Diet-restricted groups were allowed free access to food every other day, and, over the course of the study, they consumed 18-25% less than the groups allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…Leptin levels were highly correlated with OLETF body weight, fat mass and adipocyte size ( Table 2). In general, Bailey 33 reported that I-WAT mass decreased as a function of both reduced size and number of fat cells, following exercise. Thus, this tissue appears to be an energy reservoir that responds to the body's energetic needs, not only after exercise, but also in lactation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin levels were highly correlated with OLETF body weight, fat mass and adipocyte size ( Table 2). In general, Bailey 33 reported that I-WAT mass decreased as a function of both reduced size and number of fat cells, following exercise. Thus, this tissue appears to be an energy reservoir that responds to the body's energetic needs, not only after exercise, but also in lactation.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34] However, an increase can be observed in genetically obese adult animals, in response to various manipulations. 33 The inguinal fat pad is distinct from other fat depot types, as both adipocyte cell size and number can be affected by food consumption and reproductive status. 33 For this reason we further investigated the size of inguinal adipocytes.…”
Section: Tissue Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Li and colleagues (Li et al 2003) have reported that the responsiveness of lipid metabolism-related genes to fasting is more sensitive in visceral fat (including peri-renal and epididymal fat pads), and is almost unchanged in subcutaneous fat in rats. In male Wistar rats subjected to alternate-day feeding for CR, it was reported that the peri-renal fat and the epididymal fat pads, but not the inguinal fat pad, show similar age-and CR-related changes in fat cell size and number (Bailey et al, 1993). In our previous study using the epididymal fat pad in male F344 rats , the p-Akt/PKC-Glut4 pathway was upregulated at baseline in CR rats.…”
Section: Discussionmentioning
confidence: 76%
“…Os dados encontrados em relação ao grupo SR confirmam os achados da literatura, que demonstram que o processo natural do envelhecimento causa aumento de massa em ratos até meados dos 20 meses de idade (BAILEY et al, 1993;HOLLOSZY, 1997;ATHANASIOU et al, 2000;WANG et al, 2006).…”
Section: Fêmurunclassified